What do we do with chronic lymphocytic leukemia with 17p deletion? - Sellner, Leopold; Denzinger, S.; Dietrich, Sascha; Glimm, Hanno; Merkel, O.; Dreger, Peter; Zenz, Thorsten (Current hematologic malignancy reports, 2013)
Chronic lymphocytic leukemia (CLL) with 17p deletion or mutations of the TP53 gene has a very poor outcome. Optimal treatment of these patients remains a major clinical challenge, and disagreement on the optimal treatment approach exists. Conventional chemo-immunotherapy with rituximab in combination with purine analogues yields lower response-rates and less satisfactory results than for CLL patients with intact p53. Allogeneic stem cell transplantation may allow long-term remissions in this challenging group of patients. In this review, we will discuss current treatment options as well as experimental approaches in clinical trials for CLL patients with deleted or mutated TP53. Particular emphasis will be placed on novel agents with the potential to change clinical practice and future perspectives for the management of these “highest risk” patients.